(3GdeNJUQ GdaGQSj aj CYeGd GdWHs ((3eMeO Hf eMeO Gddjd s)
(3ChdgG (B:s
(3hPdc Cfg dGjfHZi dEfSGf YGbd Cf jbOe Ydi YdGL eQV ef GdCeQGV hde jJbOe dg ai Pdc OQGjI hdGSHb dg ai Pdc SGHb s
(3BNQgG (B:s
(3hjbdY CKQ GdahGcg ef GdKhGH HCf JDNP ef GdCSfGf hgh TH GdZGShd hGdbaI hGdTH hGdUeZ GdYQHi , jZSd HgG , hGddg CYde HGdUhGH s
(3hjTJed Ydi JSYI YTQ HGHkGs
(3hgh aj YdGL GdCeQGV HMSH CSHGHgG hYdGeGJgG heG jfUQa Edi Pdcs
(3, hHGdfSNI HJQ eGHjf GdhQbI(B20(3,(B21(3h(B30(3,(B31s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs